Analisis Lesbian, Gay, Bisexsual, dan Transgender (LGBT) Anggota Tentara Nasional Indonesia dalam Perspektif Hukum Pidana Militer: Kajian Berdasarkan Putusan Pengadilan - Sarwo Edy Slamet; Johny Harry Isabela Patty (Universitas Proklamasi 45, 2025)
The Indonesian National Armed Forces (TNI) are not immune to LGBT behavior, as evidenced by several military court rulings and Supreme Court decisions that have further reinforced this precedent. The purpose of this research is to understand homosexual behavior within the TNI, the processes for resolving such cases, and, in addition, to contribute ideas for addressing the related legal issues. The research method employed is a literature study of several legal sources, including primary legal materials, binding legal materials, and tertiary legal references, which serve as complementary support. Military courts have convicted TNI members engaged in homosexual acts by applying Article 103 of the Indonesian Military Criminal Code, broadening the interpretation of the phrase “official orders” to include orders related to service, encompassing the development and guidance of TNI soldiers. Furthermore, the expanded meaning of “directed to individuals” also includes orders addressed to military units, where in practice such orders are deemed to have been conveyed to members of the unit, including the defendant. The Commander of the TNI’s Telegram Letter (ST) serves as the basis for resolving cases of homosexual conduct among TNI personnel, substantively containing prohibitive norms against homosexual acts, with its classification carrying the force of an order.